Meningkatkan Bahasa Ekpresif Melalui Sapaan Pagi (Morning Talk) Di RA Al Ikhlash Cidolog - Sri Mulyani; Sofia Ratna Awaliyah Fitria; Saepul Milah (Bildung: Jurnal Ilmu Pendidikan, 2025)
This study examines the effect of Morning Talk activities on the expressive language skills of 4–5-year-old children at RA Al Ikhlash Cidolog. The study was driven by children’s difficulties in expressing ideas, feelings, and daily experiences. A quantitative approach with a Quasi-Experimental One Group Pretest–Posttest design was used, involving 11 participants. Expressive language was assessed using a 1–4 rubric (1 = Not Yet Developed, 2 = Beginning to Develop, 3 = Developing as Expected, 4 = Very Well Developed). Data were analyzed descriptively and with a paired sample t-test. Pretest results showed 63.7% of children were in the Not Yet Developed and Beginning to Develop categories, indicating low expressive ability. After the intervention, posttest scores improved significantly: 54.5% of children reached the Developing as Expected level and 36.4% the Very Well Developed level. The mean score rose from 2.18 to 3.27 (p = 0.000 < 0.05). These findings confirm that Morning Talk effectively enriches vocabulary, supports sentence construction, and builds confidence in verbal communication. Consistent with Vygotsky’s theory, the study highlights social interaction as crucial in language development and suggests Morning Talk as a simple and effective strategy in early childhood education.